The role ofAkkermansia muciniphilain obesity, diabetes and atherosclerosis. Issue 10 (October 2021) - Hasani, Alka; Ebrahimzadeh, Saba; Hemmati, Fatemeh; Khabbaz, Aytak; Hasani, Akbar; Gholizadeh, Pourya
Abstract : N/A: Alteration in the composition of the gut microbiota can lead to a number of chronic clinical diseases. Akkermansia muciniphila is an anaerobic bacteria constituting 3‐5% of the gut microbial community in healthy adults. This bacterium is responsible for degenerating mucin in the gut; its scarcity leads to diverse clinical disorders. In this review, we focus on the role of A. muciniphila in diabetes, obesity and atherosclerosis, as well as the use of this bacterium as a next‐generation probiotic. In regard to obesity and diabetes, human and animal trials have shown that A. muciniphila controls the essential regulatory system of glucose and energy metabolism. However, the underlying mechanisms by which A. muciniphila alleviates the complications of obesity, diabetes and atherosclerosis are unclear. At the same time, its abundance suggests improved metabolic disorders, such as metabolic endotoxemia, adiposity insulin resistance and glucose tolerance. The role of A. muciniphila is implicated in declining aortic lesions and atherosclerosis. Well‐characterized virulence factors, antigens and cell wall extracts of A. muciniphila may act as effector molecules in these diseases. These molecules may provide novel mechanisms and strategies by which this bacterium could be used as a probiotic for the treatment of obesity, diabetes and atherosclerosis.